Building a Prediction Model to Predict the Breast Cancer using ANN’S Kernel Based Method - G, Naganandini.; R H, Vishwanth. (International Journal of Engineering and Technology, 2018)
The most vulnerable disease is Breast Cancer. Many different  methods and processes were identified for the early detection and for the remedy  of Breast Cancer .Till date only two genes have been identified and which accounts for genetic characteristics to a large extent. A  particular variant has been identified as a major  hetrozygous component which amounts as a major component for the breast cancer. The rigorous working on Human Genome project  has proved that  the family history plays a major role in detecting Breast cancer and also helps in gaining knowledge about  genetic variations which depicts as a high risk factor among all the cancer types. The overall observation has concluded that the risk of this disease is mostly among the women community who has a family history. The ultimate aim is to classify the genes that are most significant and non-significant among all the genes present in the breast cancer tissue at the early stages using    Naïve’s Bayesian’s and c5.0 algorithm and hence build a predictor  model  to   predict breast cancer using ANN’s Kernal based method.